Healthy dietary patterns, foods, and risk of glioma: A systematic review and meta-analysis of observational studies - Shu, Long; Yu, Dan; Jin, Fubi (Frontiers in Nutrition, 2023)
Background Accumulating epidemiological evidence has shown the favorable associations between healthy dietary patterns and risk of glioma, although the results remain inconclusive. Objective We therefore carried out a systematic review and meta-analysis to summarize the evidence from previous published studies, and to clarify the effects of healthy dietary patterns, typical healthy foods on glioma. Methods PubMed, Web of Science, CNKI, and Wan fang data were searched from inception up to September 2022 for eligible studies. Two authors independently performed the literature search, study selection, data extraction, and quality assessment. Heterogeneity across studies was estimated using the Cochran’s Q test and I2 statistic. According to heterogeneity, the fixed-effects model or random-effects model was selected to obtain the relative risk (RR) of the merger. Subgroup analysis, sensitivity analysis and publication bias were also used for our analysis. Results Twenty-four articles that met the selection criteria, involving 7,278 glioma cases and 2,143,528 participants, were included in our analysis. There was a reduced risk of glioma in the highest compared with the lowest categories of healthy dietary patterns (RR = 0.58; 95% CI: 0.44–0.77; P < 0.0001). Moreover, compared with the lowest intakes, the highest intakes of vegetables (RR = 0.84; 95% CI: 0.73–0.96; P = 0.012) and fruits (RR = 0.85; 95% CI: 0.72–1.00; P = 0.045) significantly reduce the risk of glioma. However, the intakes of fresh fish, nuts, whole grains, and dairy products showed no statistically significant associations with the risk of glioma (P > 0.05). Conclusion Findings from this systematic review and meta-analysis indicate that higher intakes of healthy dietary patterns, vegetables, and fruits are significantly associated with the lower risk of glioma. Further studies, particularly with prospective design, are required to confirm our findings.